TRADISI ADOK SEBAGAI WUJUD ESTETIKA BUDAYA DALAM ADAT PERNIKAHAN - Namira, Engracia Abelta; Camellia, Camellia (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aims to examine the adok tradition as a form of cultural aesthetics within the wedding customs of the Ranau community in Sukamarga Village, South OKU Regency, Indonesia. The adok tradition is not merely a ceremonial ritual but functions as a cultural mechanism embedded with symbolic meanings, aesthetic expressions, and social legitimacy. This research employs a qualitative approach with an ethnographic design, utilizing participant observation during traditional wedding ceremonies, in-depth interviews with customary leaders, community members, and married couples, as well as documentation analysis. The findings reveal that the adok tradition represents Ranau cultural aesthetics through three interrelated dimensions: visual, performative, and symbolic aesthetics. The ngeharak kebayan procession, the use of traditional ornaments, martial arts performances accompanied by kulintang music, and the striking of the gong serve as aesthetic expressions that affirm honor, social recognition, and communal acceptance of the bride and groom. Furthermore, the adok tradition embodies noble values such as togetherness, social responsibility, protection, and respect for customary structures. From the perspective of Pancasila and Civic Education, the adok tradition holds significant relevance as a contextual learning resource grounded in local wisdom, contributing to the formation of civic identity and the internalization of Pancasila values. This study highlights the importance of preserving the Adok Tradition to ensure the sustainability of local culture amid contemporary social transformations. ABSTRAK Penelitian ini bertujuan untuk mengkaji tradisi adok sebagai wujud estetika budaya dalam adat pernikahan masyarakat Ranau di Desa Sukamarga, Kabupaten OKU Selatan. Tradisi adok dipahami bukan sekadar ritual seremonial, melainkan sebagai mekanisme adat yang sarat makna simbolik, estetika, dan fungsi sosial. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian etnografi, yang dilakukan melalui observasi partisipatif pada prosesi adat pernikahan, wawancara mendalam dengan tokoh adat, masyarakat, dan pasangan pengantin, serta studi dokumentasi adat. Hasil penelitian menunjukkan bahwa Tradisi adok merepresentasikan estetika budaya Ranau dalam tiga dimensi utama, yaitu estetika visual, performatif, dan simbolik. Prosesi ngeharak kebayan, penggunaan ornamen adat, pertunjukan kuntau dengan iringan kulintang, serta penabuhan gong menjadi ekspresi estetika yang menegaskan kehormatan, legitimasi sosial, dan penerimaan adat terhadap pasangan pengantin. Tradisi adok mengandung nilai-nilai luhur berupa kebersamaan, tanggung jawab sosial, perlindungan, dan penghormatan terhadap struktur adat. Dalam perspektif Pendidikan Pancasila dan Kewarganegaraan, Tradisi adok memiliki relevansi strategis sebagai sumber belajar kontekstual berbasis kearifan lokal yang berkontribusi pada pembentukan identitas kewargaan dan penguatan nilai Pancasila. Penelitian ini menegaskan pentingnya pelestarian tradisi adok sebagai bagian dari keberlanjutan budaya lokal di tengah dinamika sosial modern.